Pembuatan Peta Portabel Berbasis Android Smart Phone Kampus Terakreditasi di Kota Banjarmasin - Faris Ade Irawan; Effan Najwaini (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2019)
Geospatial or geographic space is a spatial aspect that shows the location, location, and position of an object or event that is below, on, or above the surface of the earth expressed in a particular coordinate system. Geospatial is widely used in various applications that aim to inform the map of a point or place to its users. Indonesia has a lot of universities both public and private. Each college has the value of Accreditation. Information on accreditation of a campus is very important to be published openly and accurately because it is related to the interests of prospective students. This study aims to create a geospatial-based application that informs the location of the college along with the accreditation value of the college. From this study a map can be installed on an Android smartphone. This map can provide geospatial information about campuses in the city of Banjarmasin accompanied by addresses and complete positions and information on accreditation status of BAN PT both the status of the Institution and the accreditation status of the study programs on the campus.